Sodium‐glucose co‐transporter‐2 inhibitor use and risk of lower‐extremity amputation: Evolving questions, evolving answers. Issue 5 (4th March 2019) - Yang, Jeff Y.; Wang, Tiansheng; Pate, Virginia; Gower, Emily W.; Crowley, Matthew J.; Buse, John B.; Stürmer, Til
Abstract : Aim: To examine whether sodium‐glucose co‐transporter‐2 (SGLT2) inhibitors are associated with a higher risk of lower‐extremity amputation than dipeptidyl‐peptidase‐4 (DPP‐4) inhibitors and sulphonylureas. Methods: We conducted a retrospective cohort study, using the MarketScan Commercial Claims and Encounters Database (2013‐2015), to compare the incidence of lower‐extremity amputation (LEA) between initiators of SGLT2 inhibitors and initiators of two second‐line drugs, DPP‐4 inhibitors and sulphonylureas (SUs). We estimated crude incidence rates (IRs) and adjusted hazard ratios (aHR), with 95% confidence intervals (CIs), before and after propensity‐score weighting. We additionally conducted sensitivity analyses using a comparator group of all non‐metformin, non‐SGLT2 inhibitor glucose‐lowering drugs, as previous studies used this approach. Results: In a cohort of 328 150 individuals aged 18 to 64 years, the IR of LEA ranged from 1.5 to 2.4 per 1000 person‐years. In as‐treated analysis, the estimated hazard of LEA was increased among SGLT2 inhibitor initiators compared to DPP‐4 inhibitor initiators (aHR 1.69, 95% CI 1.20‐2.38), but not compared to SU initiators (aHR 1.02, 95% CI 0.67‐1.55) or non‐metformin, non‐SGLT2 inhibitor initiators (aHR 1.02, 95% CI 0.54‐1.93). Results were consistent in intention‐to‐treat analysis and across a number of sensitivity analyses. Conclusions: Among commercially insured patients in the United States, our results suggest that initiation of SGLT2 inhibitors may increase the risk of LEA compared to initiation of DPP‐4 inhibitors. Contrasting results when comparing SGLT2 inhibitor initiators to DPP‐4 inhibitor and SU initiators highlight the importance of choosing appropriate comparator drugs when addressing comparative effectiveness and safety questions that can inform clinical decision‐making.